Effects of repeated-sprint training in hypoxia on tennis-specific performance in well-trained players - Brechbuhl, C.; Brocherie, F.; Millet, G. P.; Schmitt, L. (Sports Medicine International Open, 2018)
This study examined the physiological, physical and technical responses to repeated-sprint training in normobaric hypoxia [RSH, inspired fraction of oxygen (FiO2) 14.5%] vs. normoxia (RSN, FiO2 20.9%). Within 12 days, eighteen well-trained tennis players (RSH, n=9 vs. RSN, n=9) completed five specific repeated-sprint sessions that consisted of four sets of 5 maximal shuttle-run sprints. Testing sessions included repeated-sprint ability and Test to Exhaustion Specific to Tennis (TEST). TEST`s maximal duration to exhaustion and time to attain the `onset of blood lactate accumulation` at 4 mMol.L-1 (OBLA) improvements were significantly higher in RSH compared to RSN. Change in time to attain OBLA was concomitant with observations similar in time to the second ventilatory threshold. Significant interaction (P=0.003) was found for ball accuracy with greater increase in RSH (+13.8%, P=0.013) vs. RSN (-4.6%, P=0.15). A correlation (r=0.59, P<0.001) was observed between change in ball accuracy and TEST`s time to exhaustion. Greater improvement in some tennis-specific physical and technical parameters was observed after only 5 sessions of RSH vs. RSN in well-trained tennis players.